Effects of Compliant Flooring on Dynamic Balance and Gait Characteristics of Community-Dwelling Older Persons - C. Sittichoke (2019)
© 2019, Serdi and Springer-Verlag International SAS, part of Springer Nature. Background: Compliant flooring while providing the impact force attenuation in the event of falls, its low stiffness characteristic might impair balance and gait which consequently resulted in an increase in the risk of falling. Objective: To investigate the effects of compliant flooring on dynamic balance and gait performance of older adults under challenging conditions. Design and Participants: A cross-sectional designed with repeated measured. Thirty five community-dwelling older adults (mean age 74.91 ± 6.51 yrs) participated in this study. Measurement: Modified Dynamic Gait Index (mDGI) and Timed Up and Go (TUG) were used to assess dynamic balance. Spatio-temporal gait parameters were measured under comfortable and maximal speed. All tests were administered on the vinyl and compliant flooring in random order. Results: The time taken to complete TUG and the mDGI scores were similar between the two flooring types (p ≥ 0.05). Overall, gait characteristics were comparable when walking on the compliant and vinyl flooring for both speeds except for swing time, step time, and cadence. Conclusion: The present study demonstrated that compliant flooring did not significantly affect dynamic balance and had minimal effects on gait characteristics. The compliant flooring appears to be safe for installing in self-ambulating older adult’s home.